Seedling Growth of Wheat as Affected by Soil Salinity (Bangladesh Agronomy Journal, 2018)
An experiment was conducted to evaluate seedling growth of wheat under saline condition. Thirty wheat genotypes were grown in trays containing different levels of salinity (Control, 6 and 12 dSm-1) during October to December, 2013. Seedling emergence index, shoot and root length, shoot and root dry weight were found to be reduced with the increases of soil salinity level but the degree of reduction were not similar for all wheat genotypes. Salt tolerance index (STI) also indicated a wide difference in salt tolerance among the wheat genotypes. Sourav, Gourav, Shatabdi, BAW 1185, BAW 1186, BAW 1187, BAW 1189 and BAW 1193 were more salt tolerance while BAW 1177, BAW 1190 and BAW 1198 showed greater salt sensitivity than the other wheat genotypes at 6 dS m-1. However, at 12 dS m-1, Sourav, Gourav, Shatabdi, Sufi and BAW 1184 showed more salt tolerance and BAW 1183, BAW 1190, BAW 1192, BAW 1194 and BAW 97 provided greater stress sensitivity among the testing wheat genotypes. Considering both saline stress Sourav, Gourav and Shatabdi were found to be salt tolerant and BAW 1190 was saline sensitive wheat genotypes.Bangladesh Agron. J. 2017, 20(2): 53-66